2022
DOI: 10.1021/acsanm.1c04031
|View full text |Cite
|
Sign up to set email alerts
|

Copper/Silver Bimetallic Nanoparticles Supported on Aluminosilicate Geomaterials as Antibacterial Agents

Abstract: This study aims to understand how properties of modified aluminosilicate geomaterials influence the antibacterial performance of nanocomposites when prepared with bimetallic nanoparticles (NPs).Copper/silver (Cu/Ag) bimetallic NPs were synthesized in the presence of imogolite (Imo), montmorillonite (Mtt), or zeolite (Zeo) using a simple onepot method and characterized for their crystal phases, micro-and nanomorphologies, particle size, elemental composition, and electrophoretic mobility. The antibacterial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Relevant studies suggest that the incorporation of silver components significantly reduces the oxidation tendencies of CuNPs. The formation of Ag-Cu NPs reduces oxygen ingress, resulting in a more stable structure compared to monometallic conditions, allowing for slow ion release, both favorable for synergistic interactions between the two metals ( Cruces et al, 2022 ). Ahmadinejad et al investigated the aging of synthesized Ag-Cu alloy nanoparticles and found them to be more stable than pure Cu nanoparticles, attributing this stability to the protective effect of a thin Ag shell ( Ahmadinejad and Mahdieh, 2022 ).…”
Section: Outstanding Attributes and Influential Factors In Antibacter...mentioning
confidence: 99%
“…Relevant studies suggest that the incorporation of silver components significantly reduces the oxidation tendencies of CuNPs. The formation of Ag-Cu NPs reduces oxygen ingress, resulting in a more stable structure compared to monometallic conditions, allowing for slow ion release, both favorable for synergistic interactions between the two metals ( Cruces et al, 2022 ). Ahmadinejad et al investigated the aging of synthesized Ag-Cu alloy nanoparticles and found them to be more stable than pure Cu nanoparticles, attributing this stability to the protective effect of a thin Ag shell ( Ahmadinejad and Mahdieh, 2022 ).…”
Section: Outstanding Attributes and Influential Factors In Antibacter...mentioning
confidence: 99%
“…Both mono and bimetallic nanoparticles are suitable for applications in various fields, including biomedical, biosensors, nanomedicine, imaging, wastewater treatment, oil and gas industries, agriculture/food processing and gene/drug delivery [14][15][16][17][18][19][20]. In addition, antimicrobial and anticancer activities of bimetallic nanoparticles have also been investigated extensively [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Copper (Cu), one of the important trace elements in vivo, exhibits excellent antibacterial properties. , Meanwhile, it is important in many enzymatic reactions in vivo and can enhance cell viability and osteoblast proliferation, too . Currently, mainly elemental copper or copper oxide nanoparticles are studied; nevertheless, there are few studies on the incorporation of copper into nanoparticles in the form of ions. , Copper ions can replace part of calcium ions in calcium salts, and their slow release from the compound has been confirmed to be antibacterial .…”
Section: Introductionmentioning
confidence: 99%